Simulation of Real Driving Cycles of Electric Cars in Laboratory Conditions - Kucera, Lubos; Gajdosik, Tomas; Gajdac, Igor; Mruzek, Martin; Tomasikova, Maria (Communications - Scientific letters of the University of Zilina, 2017)
This article is focused on the area of research and development of vehicles with electric drive. The paper presents the results of research based on real electric vehicle EDISON EV as the real traffic in laboratory conditions reflecting. The analysis of special driving style was created in order to increase electric vehicle range.